Effect of genotypes and cropyear on thedifferent cultivation parameters of asparagus (Asparagus officinalis L.) - Erdős, Zsuzsa (Acta Agraria Debreceniensis, 2014)
The experiments were performed in the Research Institute of Nyíregyháza Research Institutes and Study Farm, Centre for Agricultural Sciences University of Debrecen of 1500 m2 asparagus plantation. The asparagus was planted in 2011. We were determine the number of shoots, plant height and fold thicknes of asparagus hybrid. We can continuously monitored the growing parameters of asparagus. The harvest of asparagus was started in 2013, so we were able to measure to quantity. The weather was characterized by warm and matched precipitation in the growing season (April–July) in 2011 and 2012. Contrarily, the weather was very hot and dry after the late frost in 2013. The Vitalim produced the largest quantity, then the Cumulus and the end of Grolim hybrid. Number of shoot and plant height sequence is identical to the previous one. The Grolim asparagus hibrid has the largest basal diameter.